Factor Related to Satisfaction with Online Learning during COVID-19 Outbreak among Public Health Students, Thailand - Kaewjai Maleelai; Pakin Chaichuay (Ilmu Inovasi Nusantara, 2022)
During the outbreak, all educational institutions turned to online learning to reduce the risk of infection and prevent the spread of COVID-19. A cross-sectional study design aimed to study factors related to satisfaction with online learning during the COVID-19 outbreak among Public Health students. A total of 163 students of Bachelor of Public Health students from the Sirindhorn College of Public Health in Ubon Ratchathani province, Thailand, were included in our study. We gathered data from May to June 2021. An online survey for the COVID-19 outbreak was used to gather data. We calculated descriptive statistics; frequency, percentage, mean, and standard deviation. We analysed the data using descriptive statistics and computed the independent t-test to understand the relationship between variables. We found that majority of the participants were female (82.8%). Participants studied either a Community Public Health program (54.0%) or a Dental Public Health program (46.0%). Most participants used computer notebooks (79.8%) for online study. Google Classroom was the most frequently used online learning platform (98.2%). Overall, online learning was found moderately satisfying (mean=3.300, S.D.=0.920). There was a statistically significant difference (p<0.05) in the mean satisfaction scores compared to gender and two major programs. When comparing satisfaction with online learning between gender and two major programs, we found that there were statistically significant differences in online learning methods, contents of the curriculum, supporting factors, an evaluation, and the instructor. Additional supporting factors were no statistically significant differences between the two major programs